2013
DOI: 10.1021/jo401763v
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement Reactions of Lithiated Oxiranes

Abstract: The first computational study of the rearrangement reactions of oxiranes initiated by lithium dialkylamides is presented. Aside from the well-known carbenoid insertion pathways, both β-elimination and α-lithiation have been suggested as the exclusive mechanism by which oxiranes react in the presence of organolithium bases. The products of the former are allyl alcohols (and, in some cases, dienes) and are ketones in the case of the latter. The computational studies reported in this work indicate that both mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In this context, it should be noted that ring-lithiated oxiranes are known to rearrange to enolates. 24,25 This reaction has been studied computationally 26,27 and has a relatively high activation energy (≈ 30 kcal mol −1 ). In view of the much lower oxophilicity of Rh compared to Li, it is perhaps not surprising that oxiranylrhodium species would not readily rearrange to enolates.…”
Section: Dft Results For Oxirane Openingmentioning
confidence: 99%
“…In this context, it should be noted that ring-lithiated oxiranes are known to rearrange to enolates. 24,25 This reaction has been studied computationally 26,27 and has a relatively high activation energy (≈ 30 kcal mol −1 ). In view of the much lower oxophilicity of Rh compared to Li, it is perhaps not surprising that oxiranylrhodium species would not readily rearrange to enolates.…”
Section: Dft Results For Oxirane Openingmentioning
confidence: 99%
“…The last statement of the first paragraph of the Introduction of ref states that the reaction of 1,2-epoxy-5-hexene with lithium 2,2,6,6-tetramethylpiperidide (LTMP) leads to the aldehyde, presumably by the keto–enol isomerization of the vinyl alcohol. However, in 2004, Hodgson et al reported that terminal epoxides in the presence of hindered lithium amides like LTMP formed the enamine almost exclusively by trapping of the lithiated epoxide by the lithium amide .…”
mentioning
confidence: 99%
“…In contrast to the ring-opening considered in Scheme 2 of ref , which was at the β-carbon with respect to the deprotonated center, the α-ring-opening mechanism is also known. This latter pathway involves the formation of carbenes or carbenoids, leading to vinyl alcohols (and ketones) directly in certain cases , and allyl alcohols if the α-deprotonation is followed or accompanied by a 1,2 H-transfer .…”
mentioning
confidence: 99%
See 1 more Smart Citation